2021
DOI: 10.1021/acs.energyfuels.1c00654
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Mechanisms of Acidic Crude Oil–Aqueous Solution Interaction in Low-Salinity Waterflooding

Abstract: Crude oil−aqueous solution interactions play an important role in low-salinity waterflooding, but their effects and mechanisms have not been well clarified. Core flooding experiments were first conducted to analyze the effects of crude oil− aqueous solution interactions on enhanced oil recovery (EOR). Then, interfacial tension (IFT) and interfacial dilatational rheology (IDR), total organic carbon (TOC), and ζ-potential measurements were combined to investigate the mechanisms of crude oil− aqueous solution int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 62 publications
2
9
0
Order By: Relevance
“…SDBS desorption was enhancing through the substitute adsorption of Na in the LSW. This is well agreed with Chai et al [37], who addressed that the ionic composition has a great influence on crude oil-aqueous solution interaction, so the reduction of Na in the aqueous phase further improves the effectiveness of desorbed SDBS on the crude oil-aqueous interface. The Na desorption in LSW-SDBS-LSW however affects the effectiveness of SDBS in the post-flush.…”
Section: Chemistry Of Effluent and Iftsupporting
confidence: 89%
“…SDBS desorption was enhancing through the substitute adsorption of Na in the LSW. This is well agreed with Chai et al [37], who addressed that the ionic composition has a great influence on crude oil-aqueous solution interaction, so the reduction of Na in the aqueous phase further improves the effectiveness of desorbed SDBS on the crude oil-aqueous interface. The Na desorption in LSW-SDBS-LSW however affects the effectiveness of SDBS in the post-flush.…”
Section: Chemistry Of Effluent and Iftsupporting
confidence: 89%
“…Chai et al' results revealed that Mg 2+ and Ca 2+ both had positive effects on EOR, while SO 4 2− showed no positive effect through adjusting crude oil−aqueous solution interactions in low salinity waterflooding. 121 Other important results related with water modification of carbonate came form Zhang et al's research. They consider that reactivity of the surface of biogenic chalk is much higher than for recrystallized limestone.…”
Section: Potential Ions Modifying the Wettability Of Carbonatementioning
confidence: 98%
“…In addition, it is noted that the mechanism is strongly dependent on temperature, in which temperature has a great influence on dehydration of Mg 2+ and Ca 2+ , and Mg 2+ became much more reactive in eqs and . Chai et al’ results revealed that Mg 2+ and Ca 2+ both had positive effects on EOR, while SO 4 2– showed no positive effect through adjusting crude oil–aqueous solution interactions in low salinity waterflooding …”
Section: Potential Ions Modifying the Wettability Of Carbonatementioning
confidence: 99%
“…Much of the prior research has proven fluid–rock interaction as the primary consideration for improving oil recovery. The fluid–fluid interactions on low salinity effect have recently received more attention. Chai et al have shown the relation between the ionic composition of the injected brines and oil recovery through coreflooding experiments . Some research has found relations between oil recovery improvement and an increase in interfacial elasticity. For instance, Garcia-Olvera et al demonstrated that low salinity brine made a more elastic interfacial film with crude oils.…”
Section: Introductionmentioning
confidence: 99%
“…25−27 Chai et al have shown the relation between the ionic composition of the injected brines and oil recovery through coreflooding experiments. 28 Some research has found relations between oil recovery improvement and an increase in interfacial elasticity. 29−31 For instance, Garcia-Olvera et al 31 demonstrated that low salinity brine made a more elastic interfacial film with crude oils.…”
Section: Introductionmentioning
confidence: 99%